Black Soldier Fly Larvae Cultivation: A Sustainable Solution for Organic Waste in in Tanjung Karang and Taman Dato’ Harun Communities in Malaysia - Suhartini, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Malaysia faces significant challenges in food waste management, with approximately 8,000 tons of food waste generated daily, only 5% of which is treated. To address this issue, the